PENGARUH PROFITABILITAS, GROWTH, LIKUIDITAS, RISIKO BISNIS DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2020 - Indy Sekar Sari; Nungki Pradita (JURNAL ILMIAH EDUNOMIKA, 2021)
Debt policy is a strategy that will be taken by company insiders to be able to determine the debt funding that the company wants to take. The purpose of this study was to examine the variables of profitability, growth, liquidity, business risk, and managerial ownership of debt policy. All manufacturing companies for the 2017-2020 period listed on the IDX are used as the population in this study. The sample with total acquisition is 128 samples with 32 companies with 4 years of observation. Sampling was obtained using purposive sampling technique. Multiple linear regression is a technique for testing this research. The results obtained from this test are that profitability, liquidity, and managerial ownership indicate that there is a negative and significant effect on debt policy, growth indicate that there is a positive and significant effect on debt policy, and business risk indicate that there is a negative but not significant effect on debt policy. Keywords : Profitability, Growth, Liquidity, Business Risk, and Managerial Ownership